Answer:
(8, 6 )
Explanation:
Given the 2 equations
2x + 3y = 34 → (1)
3x + 2y = 36 → (2)
Multiplying (1) by 3 and (2) by - 2, then adding will eliminate the x- term
6x + 9y = 102 → (3)
- 6x - 4y = - 72 → (4)
Add (3) and (4) term by term to eliminate x, that is
5y = 30 ( divide both sides by 5 )
y = 6
Substitute y = 6 into either of the 2 equations and solve for y
Substituting into (1)
2x + 3(6) = 34
2x + 18 = 34 ( subtract 18 from both sides )
2x = 16 ( divide both sides by 2 )
x = 8
solution is (8, 6 )